Clinical Significance of Galactose-Deficient IgA1 by KM55 in Patients with IgA Nephropathy - Kai Zhang; Qiongqiong Li; Yaru Zhang; Wenya Shang; Li Wei; Hongfen Li; Shan Gao; Tiekun Yan; Junya Jia; Youxia Liu; Shan Lin (Karger Publishers, 2019)
Background: Aberrant galactose-deficient IgA1 molecules (Gd-IgA1) are important causal factors in IgA nephropathy (IgAN); however, the detection of Gd-IgA1 in IgAN is complicated and instable. A monoclonal antibody, KM55, which specifically recognizes Gd-IgA1 has been developed. In the present study, we further explored the clinical significance of Gd-IgA1 using KM55. Methods: In this study, we enrolled 75 patients with IgAN and 80 healthy controls and detected the plasma Gd-IgA1 levels using the KM55 ELISA method. We also stained mesangial Gd-IgA1 deposition using KM55. Results: We observed that the levels of plasma Gd-IgA1 in IgAN patients were elevated compared to the corresponding levels of healthy controls. Patients were divided into 2 groups based on the median of Gd-IgA1. Patients with high Gd-IgA1 levels had significantly higher levels of uric acid (UA) and IgA. The other clinical manifestations demonstrated that there were no differences in age, sex, blood pressure, initial proteinuria, hematuria, estimated glomerular filtration rate and Oxford pathological classification between the 2 groups of patients. In addition, positive correlations were observed between Gd-IgA1 and Bb, C3a, C4d and MAC. Mesangial Gd-IgA1 was positive in IgAN but negative in the normal renal tissue adjacent to neoplasm. We next analyzed the correlation between plasma Gd-IgA1 and mesangial Gd-IgA1 deposition. The results showed that a high level of plasma Gd-IgA1 was related to the deposition of mesangial Gd-IgA1, although the difference was not significant. Conclusion: We verified the elevated level of plasma and mesangial Gd-IgA1 in patients with IgAN by KM55, which provided an alternative, easy, and reliable tool for diagnosis and activity assessment of IgAN. The level of plasma Gd-IgA1 positively correlated with levels of UA, total IgA levels, and complement activation products.